Penerimaan Teknologi Artificial Intelligence (AI) dalam Ruang Redaksi Media Televisi Lokal : Studi Kasus pada Jurnalis di Kompas TV Jawa Barat - Sabila Putri Afifah; Abie Besman; M. Z. Al Faqih (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
This study examines the acceptance of Artificial Intelligence (AI) technology in the newsroom of Kompas TV Jawa Barat. It aims to analyze how journalist at Kompas TV Jawa Barat perceive and adopt AI technology in their journalistic work practices, drawing on the Technology Acceptance Model (TAM) as a theoretical framework. This study employs a qualitative approach using a case study method. The findings indicate that: 1) Journalist construct their perceived ease of use at a moderate to high level; however, its effectiveness depends on each individual’s digital literacy and prompting skills; 2) Perceived usefulness is rated as high yet selective. AI is primarily utilized for pre-coverage research, script production, digital content optimization, and protecting organizational assets from the risk of copyright infringement; 3) The acceptance of AI at kompas TV Jawa Barat is shaped by the Key Performance Indicator (KPI) policies at Kompas TV, the organizational work culture at Kompas TV Jawa Barat, journalistic ethics as a social filter, and perception of the threat posed by media disruption. This study concludes that journalist at Kompas TV Jawa Barat position AI as a supporting instrument rather than a replacement for core editorial processes, with acceptance that is both complex and contextual. These findings imply the need for an inclusive AI literacy program as well as the establishment of AI implementation guidelines for journalist at Kompas TV Jawa Barat.